2022
DOI: 10.1186/s40478-022-01375-y
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe microglia, neurodegenerative protein accumulation, and cognitive function in people with HIV

Abstract: Microglia are implicated in Alzheimer’s Disease (AD) pathogenesis. In a middle-aged cohort enriched for neuroinflammation, we asked whether microgliosis was related to neocortical amyloid beta (A$$\upbeta$$ β ) deposition and neuronal phosphorylated tau (p-tau), and whether microgliosis predicted cognition. Frontal lobe tissue from 191 individuals autopsied with detectable (HIV-D) and undetectable (HIV-U) HIV infection, and 63 age-matched controls were examined. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Whereas 39% described intravenous drug use (IVDU) as an HIV risk, 85% endorsed a lifetime substance use disorder (SUD). At autopsy, 58% had p-tau containing neurons in their brain, and 29% parenchymal Aβ plaque; as published previously, the majority of plaques were diffuse, and both pathologies were generally modest in the majority of brains analyzed [18]. In the 78 individuals displaying neuronal p-tau, distribution was restricted to entorhinal cortex in 35%, extended into hippocampal formation in 23%, and was neocortical in 42%.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Whereas 39% described intravenous drug use (IVDU) as an HIV risk, 85% endorsed a lifetime substance use disorder (SUD). At autopsy, 58% had p-tau containing neurons in their brain, and 29% parenchymal Aβ plaque; as published previously, the majority of plaques were diffuse, and both pathologies were generally modest in the majority of brains analyzed [18]. In the 78 individuals displaying neuronal p-tau, distribution was restricted to entorhinal cortex in 35%, extended into hippocampal formation in 23%, and was neocortical in 42%.…”
Section: Resultssupporting
confidence: 59%
“…We also demonstrated associations between APOE allele status, age, duration of HIV disease and Aβ deposition, and between diabetes mellitus and neuronal p-tau. In these studies, neuroinflammation did not show a predictive effect for abnormal protein deposition [18,28]. The current study used a smaller sample and was focused on determining the contributions of Aβ and p-tau to cognitive impairments; in establishing these relationships, we also found that HIV-associated variables (viremia and duration of HIV disease) and comorbidities (SUD, WRAT-3 reading levels, and diabetes) contributed to cognitive outcomes, highlighting the complexity of neurobehavioral outputs, which transcend a single protein deposition or clinical factor.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, this translates to increased susceptibility to age-related neuropathogenesis such as Alzheimer’s disease (AD) and its precursor, amnestic mild cognitive impairment (aMCI) ( Althoff et al, 2022 ). Indeed, multiple studies from independent labs have implicated age-related proteinopathies in neuropathogenesis in PWH ( Achim et al, 2009 ; Gisslen et al, 2009 , 2019 ; Chen et al, 2014 ; Fields et al, 2018 , 2020 ; Murray et al, 2022 ). Consequently, there is a need to better understand mechanisms of age-related neuropathogenesis in PWH.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of frontal cortex (FC) samples from PWH, Aβ plaques were detected in 29% of 279 cases ( Umlauf et al, 2019 ). To date, numerous studies have provided evidence of AD-related neuropathogenesis in HIV ( Chen et al, 2014 ; Fields et al, 2018 ; Gisslen et al, 2019 ; Chemparthy et al, 2021 ; Murray et al, 2022 ), and thus, there is a need to better understand the common neuropathogenic mechanisms in AD and HAND.…”
Section: Introductionmentioning
confidence: 99%